A Critical Review on Adolescent Health Indicators: The Importance of Comprehensive Measurement - 권미영 (Korean Journal of Social Quality, 2023)
This paper conducts a critical review on the existing health indicators in South Korea. The review is part of measures to pinpoint the health status of adolescents in South Korea. The health indicators for adolescents in South Korea have relied on physical health indicators such as obesity and emotional/psychological health indicators such as depression. That is, there have been an insufficient number of indicators to comprehensively measure the health status of adolescents in terms of physical, psychological, and social aspects. This reality is what the study will closely examine and the study will also emphasizes the need for health indicators that attempt to comprehensively measure adolescents’ health. And as a way to do this, this paper pays attention to ‘self-rated health’. This paper consists of three parts. The first part explores the current status of related issues in order to understand the current state of health measurement for adolescents in South Korea. The second part reviews the existing major indicators (e.g. depression, self-esteem) in relation to adolescent health measurement. The third part examines self-rated health (i.e. subjective health status perception) that seeks comprehensive health measurement and this is for improving the level of health measurement for adolescents. KCI Citation Count: 0